2019
DOI: 10.26873/svr-740-2019
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide Hepatotoxicity: The Role of 4-Hydroxynonenal and Cytochrome C Oxidase and the Possible Protective Effect of Ganoderma Lucidum Extract

Abstract: Cyclophosphamide (CPA) is a widely used anti-neoplastic drug, but its usage is associated with several side effects including hepatotoxicity. This study was designed to evaluate the ameliorative effect of Ganoderma lucidium (GL) extract as a natural antioxidant against CPA hepatotoxicity in male Wistar albino rats. Four groups of rats (n = 7) were used in this study, Group I: served as a control group, group II: was administrated CPA (5 mg/kg), group III: received GL extract (50 mg/kg), and group IV: received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…Treatment with CPMD is associated with bone marrow suppression and pancytopenia, which might be the reason for such an effect on platelet count. The previous report showed that the alterations in the levels of albumin and globulin caused by CPMD were due to a decrease in protein synthesis as a result of liver damage [25,26]. Herein, the EAPL treatment prevented liver damage and increased the levels of albumin and globulin.…”
Section: Discussionmentioning
confidence: 86%
“…Treatment with CPMD is associated with bone marrow suppression and pancytopenia, which might be the reason for such an effect on platelet count. The previous report showed that the alterations in the levels of albumin and globulin caused by CPMD were due to a decrease in protein synthesis as a result of liver damage [25,26]. Herein, the EAPL treatment prevented liver damage and increased the levels of albumin and globulin.…”
Section: Discussionmentioning
confidence: 86%
“…La causa principal de esta toxicidad son las especies reactivas de oxígeno que se generan durante su metabolismo. Esta acción puede ser potenciada por su metabolito activo, llamado acroleína, el cual puede reaccionar con el glutatión hepático, ocasionando su agotamiento; en adición, aumenta la susceptibilidad de peroxidación lipídica y la lesión de los tejidos hepáticos [22].…”
Section: Ciclofosfamida Y Azatioprinaunclassified